Measuring the impact of information aggregation mechanisms: An experimental investigation - Bennouri, Moez; Gimpel, Henner; Robert, Jacques (Journal of economic behavior & organization, 2011)
► We compare the effectiveness of market-based and cheap-talk information aggregation mechanisms (IAM). ► In a laboratory experiment, we study how information provided by IAMs interacts with private and public information and affect bidding behavior in a multi-unit common-value uniform-price auction. ► In market-based IAMs, information gathering prevails and subsequent bidding shows that subjects acknowledge the precision of information. ► In cheap-talk IAMs, there is almost no transmitted information. This paper measures the effectiveness of market-based and cheap-talk information aggregation. Both information aggregation mechanisms (IAMs) are frequently used prior to IPOs and sales of Treasury bonds – it is largely acknowledged that they provide agents with useful information for subsequent bidding. In a laboratory experiment, we study how information provided by IAMs interacts with private and public information and how agents integrate it in their strategic behavior in a multi-unit common-value uniform-price auction. In market-based IAMs, information gathering prevails and subsequent bidding shows that subjects acknowledge the precision of information. However, in cheap-talk IAMs, there is almost no transmitted information.